Common variation in the CD36 (fatty acid translocase) gene is associated with left-ventricular mass. - Hall, D; Mayosi, B; Rahman, T; Avery, P; Watkins, H; Keavney, B (2011)
AIMS: Genetic variation in the fatty acid translocase (CD36) gene has been shown in animal models to affect several risk factors for the development of left-ventricular hypertrophy, but this phenotype has not, thus far, been investigated in humans. We examined the relationship between common genetic polymorphisms in the CD36 gene and left-ventricular mass. METHODS AND RESULTS: We studied a cohort of 255 families comprising 1425 individuals ascertained via a hypertensive proband. Seven single-nucleotide polymorphisms which together tagged common genetic variation in the CD36 gene were genotyped using a SEQUENOM MALDI-TOF instrument. There was evidence of association between the rs1761663 polymorphism in intron 1 of the CD36 gene and left-ventricular mass determined either by echocardiography (P=0.003, N=780) or electrocardiography (P=0.001, N=814). There was also association between rs1761663 genotype and body mass index (P<0.001, N=1354). Genotype was associated with between 2 and 8% differences in these phenotypes per allele. After adjustment for the effect of body mass index, there remained significant associations between genotype and left ventricular mass measured either by echo (P=0.017) or ECG (P=0.007). CONCLUSIONS: Genotype at the rs1761663 polymorphism has independent effects both on body mass index and left-ventricular mass. Genes with such pleiotropic effects may be particularly attractive therapeutic targets for interventions to modify multiple risk factors for cardiovascular events.